Activation cross sections for reactions induced by 14 MeV neutrons on natural titanium. (March 2023) - Tang, X.; Tian, G.; Huang, Y.; Ran, J.; Wen, Z.; Xu, J.; Song, S.; Liu, B.; Han, R.; Shi, F.; Zhang, X.; Sun, H.; et al.
Abstract: Cross sections for the neutrons around 14 MeV interaction with natural titanium were precisely measured by neutron activation and off-line measurement technique. The fast neutrons were produced by 3 H(d, n) 4 He reaction and the neutron energy was obtained by using the cross section ratio method of 90 Zr(n, 2n) 89 Zr to 93 Nb(n, 2n) 92 m Nb reactions. Experimental cross sections have been acquired for nat Ti(n, x) 46 Sc, nat Ti(n, x) 47 Sc, 50 Ti(n, x) 47 Ca and 48 Ti(n, x) 48 Sc reactions. The measured cross section data are compared with the experimental data available in the previous literature and evaluated nuclear data from the ENDF/B-VIII.0, JEFF-3.3, JENDL-5, BROND-3.1, CENDL-3.2 and FENDL-3.2b libraries. Furthermore, excitation functions for these reactions were calculated by using the theoretical model based on Talys-1.96 code with default and adjusted parameters. Within experimental error, evaluated nuclear data are mostly consistent with experimental data. The excitation function with adjusted parameters can roughly reproduce the experimental data. Highlights: Cross sections of neutron induced reactions on titanium were measured. Excitation functions were calculated by Talys-1.96 code with different parameters. Experimental data are compared with evaluated nuclear data of different libraries.